A Narrative Review of Different Hemostatic Materials in Emergency Treatment of Trauma - Xiaoxiao Xiao; Zhoupeng Wu (Emergency Medicine International)
Hemostatic materials are very important for the treatment of a large number of bleeding trauma patients in battlefield and disaster environments. Different types of hemostatic materials need to be used for emergency hemostasis according to different injury parts and severity. At present, the first-aid hemostatic materials have been well applied to the bleeding of body surface wounds, limbs, and junctions, but there are still no ideal hemostatic materials in the early treatment of first aid for the deep and incompressible bleeding of thoracoabdominal cavity and visceral organs. This paper reviews the classification and mechanism of hemostatic materials, as well as the application and research progress in trauma emergency, so as to provide reference for the application of hemostatic materials in early first-aid emergency.